2023
DOI: 10.1186/s12913-023-09379-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation analysis of a case management intervention for people with complex care needs in primary care: a multiple case study across Canada

Abstract: Background Case management is one of the most frequently performed interventions to mitigate the negative effects of high healthcare use on patients, primary care providers and the healthcare system. Reviews have addressed factors influencing case management interventions (CMI) implementation and reported common themes related to the case manager role and activities, collaboration with other primary care providers, CMI training and relationships with the patients. However, the heterogeneity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The CCM played a crucial role in keeping (temporal) resources available for what HCSs are professionally trained and qualified to work on. However, there remains a challenge in finding solutions to the dilemma faced by HCSs regarding their wish to be informed about CCM procedures and linked with each other, while also managing the strain of additional requests and contact with the CCM due to limited (time) resources [ 62 ]. Hudon et al (2023) suggest that optimizing time resources and improving exchange could involve meetings, information sharing via fax, e-mail, secure online platforms, or, prospectively, within the electronic patient record (EPR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCM played a crucial role in keeping (temporal) resources available for what HCSs are professionally trained and qualified to work on. However, there remains a challenge in finding solutions to the dilemma faced by HCSs regarding their wish to be informed about CCM procedures and linked with each other, while also managing the strain of additional requests and contact with the CCM due to limited (time) resources [ 62 ]. Hudon et al (2023) suggest that optimizing time resources and improving exchange could involve meetings, information sharing via fax, e-mail, secure online platforms, or, prospectively, within the electronic patient record (EPR).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study suggest that the cross-sectoral long-term advocacy CCM in the COCOS-MS trial, with continuous personal contacts at short intervals and constant reevaluation of needs, problems, resources and goals, is highly valued by PwsMS, caregivers, and HCSs. The trial addresses several key aspects that may have been overlooked in previous studies which have shown great potential for the integration of case management [ 17 , 47 , 62 , 65 , 66 ]. However, they often excluded the overriding care management, missed those patient groups with special severity and complexity who might struggle to reach social and health care structures independently or the interventions were not intended for long-term [ 22 , 37 ].…”
Section: Discussionmentioning
confidence: 99%